Posttraumatic arachnoid cyst rupturę and delayed acute subdural hygroma - Erok, Berrin; Kıbıcı, Kenan (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Introduction. Subdural hygromas (SDGs) are the accumulation of fluid in the subdural space. Arachnoid cysts (ACs) on the other hand are common cerebrospinal fluid (CSF) containing lesions of the central nervous system, located within the subarachnoid space. They are generally found incidentally on neuroimaging studies and remain asymptomatic throughout the life. Rupture into the subdural space resulting in subdural hygroma (SDG) is relatively rare. Aim. We aimed to show the importance of the radiological follow up in head trauma patients having large ACs. Description of the case. We report a case of a 69-year-old male patient with a known large Galassi type III AC, presented to our hospital with traumatic brain injuries and re-presented with acute posttraumatic SDG in association with AC rupture. Conclusion. This case emphasizes the importance of radiological follow up in head trauma patients having large ACs to reveal and appropriately manage traumatic subdural collections.
Keywords: acute subdural hygroma; arachnoid cyst rupture; delayed subdural collection